Real‐time monitoring of greenhouse gas emissions with tall chambers reveals diurnal N2O variation and increased emissions of CO2 and N2O from Miscanthus following compost addition. Issue 12 (18th October 2019) - Keane, J. Ben; Morrison, Ross; McNamara, Niall P.; Ineson, Phil
Abstract: Miscanthus x giganteus 's efficacy as an energy crop relies on maintaining low greenhouse gas (GHG) emissions. As demand for Miscanthus is expected to rise to meet bioenergy targets, fertilizers and composts may be employed to increase yields, but will also increase GHG emissions. Manipulation experiments are vital to investigate the consequences of any fertilizer additions, but there is currently no way to measure whole‐plant GHG fluxes from crops taller than 2.5 m, such as Miscanthus, at the experimental plot scale. We employed a unique combination of eddy covariance (EC), soil chambers and an entirely new automated chamber system, SkyBeam, to measure high frequency (ca. hourly) fluxes of carbon dioxide (CO2 ), methane (CH4 ) and nitrous oxide (N2 O) from a Miscanthus crop amended with green compost. Untreated controls were also monitored in a fully replicated experimental design. Net ecosystem exchange (NEE) of CO2 was partitioned into soil respiration ( R s ), gross primary productivity (GPP) and ecosystem respiration, and the crop was harvested to determine the effect of compost on crop productivity. Compost increased NEE emissions by 100% ( p < .05), which was the result of a 20% increase of R s ( p < .06) and a 32% reduction in GPP ( p < .05) and biomass of 37% ( p < .06). Methane fluxes were small and unaffected by compost addition. N2 O emissions increased 34% under compost during an emission event; otherwise, fluxes were low and often negative, even under dry conditions. Diurnal variation in N2 O fluxes, with uptake during the day and emission at night was observed. These fluxes displayed a negative relationship with soil temperature and a hitherto undescribed diurnal temperature hysteresis. We conclude that compost addition negatively affected the productivity and environmental effects of Miscanthus cultivation during the first year following application. Abstract : We used novel technology, SkyBeam, to measure greenhouse gas emissions in near real‐time from Miscanthus following compost addition. We found that compost addition increased emissions of carbon dioxide and nitrous oxide and decreased crop productivity. The high frequency data also revealed a previously unreported diurnal pattern in N2 O fluxes, with net uptake during the day and net emissions at night time.